Subependymoma of the Cerebellopontine Angle and Prepontine Cistern in a 15-Year-Old Adolescent Boy - Koral, K.; Kedzierski, R.M.; Gimi, B.; Gomez, A.; Rollins, N.K. (American Journal of Neuroradiology, 2008)
SUMMARY: A case of cerebellopontine angle and prepontine cistern subependymoma in a 15-year-old adolescent boy is presented with a review of the literature. Apparent diffusion coefficient values for subependymoma are reported. Differential considerations for the unusual location of this rare tumor are discussed.